Gopher tortoise (Gopherus polyphemus) resource selection within a private working pine (Pinus spp.) forest landscape - Marshall, Craig D.; Maerz, John C.; Larsen-Gray, Angela L.; Chamberlain, Michael J.; Martin, James A. (Forest ecology and management, 2022)
•The strongest predictor of selection was distance to permanently open areas.•Selection was greatest proximate to permanently open areas.•Elevation and suitable soils were the second strongest predictors of selection. Private working forest landscapes provide wildlife habitat and understanding how species interact with these landscapes is critical to identifying conservation opportunities. The gopher tortoise (Gopherus polyphemus; hereafter, tortoise) is a species endemic to the Coastal Plain ecoregion of the southeastern United States, with private working pine (Pinus spp.) forests encompassing a substantive portion of area within the species’ range. Although private working pine forests contain tortoises, uncertainty exists about how tortoises use these landscapes. Specifically, there is limited information regarding tortoise habitat associations within these landscapes relative to current forest management practices. Therefore, we used radio telemetry data from 55 adult tortoises collected over 3 years to estimate resource selection within a private working forest landscape dominated by planted loblolly pine (Pinus taeda) stands in the Upper Coastal Plain ecoregion of Georgia, USA. The strongest predictor of resource selection by tortoises was proximity to permanently open areas, specifically a utility right-of-way and areas adjacent to unpaved forest roads and, to a lesser extent, areas of higher elevation containing soils suitable for tortoises. On our study area, we identified permanently open areas as an important landscape component to adult tortoises. Although adult tortoises persist within these landscapes, more work is needed to understand tortoise recruitment in private working pine forest landscapes.